1987
DOI: 10.1159/000249006
|View full text |Cite
|
Sign up to set email alerts
|

Nevus comedonicus with Epidermolytic Hyperkeratosis

Abstract: A 7-year-old girl had a linear nevus comedonicus affecting the right upper limb. Histologic examination of two biopsies specimens showed both the common changes of nevus comedonicus and the presence of epidermolytic hyperkeratosis. Therefore, nevus comedonicus should be included in the list of dermatoses having the distinctive histologic pattern of epidermolytic hyperkeratosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…In EHK, a mutation in K1 or K10 interferes with the heterodimeric pairing and gives rise to the characteristic clumping of KIFs in suprabasal layers of the epidermis 14,15 . Although many authors have mentioned the finding of EHK in some lesions of NC, we have found only eight cases reported 3,16–19 …”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…In EHK, a mutation in K1 or K10 interferes with the heterodimeric pairing and gives rise to the characteristic clumping of KIFs in suprabasal layers of the epidermis 14,15 . Although many authors have mentioned the finding of EHK in some lesions of NC, we have found only eight cases reported 3,16–19 …”
Section: Discussionmentioning
confidence: 65%
“…Four cases of NCEHK were reported by Barsky et al, 3 two of which were linear in distribution, and the other two were patchy with extensive skin involvement. In 1987, Aloi and Molinero 19 reported a case of a 7‐year‐old girl who had NCEHK in a band‐like pattern distributed over the right lower limb. Machado et al 16 recently described a similar case of a 15‐month‐old girl who presented with two linear lesions on her thigh.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis is confirmed by the characteristic histopathologic findings. Epidermolytic hyperkeratosis (3) and trichilemmal cysts (4) are associated histopathologic findings. The presence of nodular lesions may indicate trichilemmal cysts.…”
Section: Discussionmentioning
confidence: 99%
“…Since 1970, when Ackerman 6 first proposed the idea of incidental EH, many reports of EH have been published including that in association with varied nevi, 7–11 squamous cell carcinoma, 6,12,13 basal cell carcinoma, 8,13 melanoma, 8 epidermolytic acanthoma, 8 seborrheic keratosis, 6,8 scar, 8,14 leukoplakia, 15 and nevus comedonicus 16 . Although EH can be found repeatedly in the literature in association with a number of lesions, it has not been described in association with an infundibular cyst since a report by Mehregan 14 in 1978, which was the first as well as last published report.…”
mentioning
confidence: 99%